Implementation Of Problem Based Learning (PBL) In Improving Results In The Learning Of The Beauty Of Togetherness In MIS Nurul Ulum Probolinggo - Peti Zamhariro; Faisal Faliyandra; Devy Habibi Muhammad (al-Afkar, Journal For Islamic Studies, 2023)
Various empirical analyzes state that Indonesia has not fully improved its education. This is a challenge for academics to look for formulations when the problems have not fully improved, but are presented to thematic learning. Then thematic learning becomes a new challenge for classroom teachers at the basic education level. So the purpose of this study is to find a learning model formulation, namely Problem Based Learning (PBL) in overcoming the decline in learning outcomes in the theme material. Therefore we use Classroom Action Research (CAR) to focus more on class problems. For the subject in class IV with a total of 12 students with a focus on material for Sub Theme 2, Theme 1 The Beauty of Togetherness. From the results of the research conducted, it can be concluded that PBL is very effective in increasing learning outcomes for Theme 1 The Beauty of Togetherness, and Sub-Theme 2. However, the use of more cycles is also highly recommended to see the effectiveness of this learning model. For more details, see the research we have written.